The Shadow Economy : an International Survey - Schneider, Friedrich (Cambridge University Press, 2013)
Presents new data to give an overview of shadow economies from OECD countries and propose solutions to prevent illicit work.- Resumé vydavatel
Keywords: šedá ekonomika; daňové úniky; korupce; podniky; hospodářské trestné činy; informal sector (economics); tax evasion; corrupt practices; business enterprises; commercial crimes; elektronické knihy; statistiky; electronic books; statistics